Comparison of Different Coagulants for Removal of Phenol from Aqueous Solution - Rana, Saraswati; Suresh, S. (Asian Journal of Chemistry, 2015)
In today’s World with the degradation of environment, waste management has become important for sustainable development. Attempts were made in this study to examine the performance of coagulation and flocculation process using different coagulants [FeCl3, alum, FeSO4, polyaluminium chloride (PAC), tamarind seed powder, chitosan, xanthum gum] and polyelectrolyte for removal of phenol from aqueous solution. Also, the optimum conditions for coagulation/flocculation process, such as coagulant dose, pH solution, contact time, settling time, initial concentration and temperature were investigated using jar-test experiment. The results revealed that the optimal operating pH were 2, 4,6,4,6,4,8 and 5.8 for tamarind seed powder, FeCl3, FeSO4, alum, polyaluminium chloride, chitosan, xanthum gum and without coagulant, respectively. A maximum percentage removal of phenol was found to be 75 by addition of 100 mg/L polyelectrolyte. The sludge produced, when tamarind seed powder was used solely, was higher compared to the use of combination of polyelectrolyte and tamarind seed powder. The combined use of coagulant and polyelectrolyte resulted in the production of sludge with reduction of 76.3 % of the amount produced.